Ameliorative Effect of Tamarindus indica and Vitamin D Supplementation On Fluoride Induced Biochemical Parameters in Albino Rat - Shalini Yadav; P.K. Singh, Prem Sagar; Harendra Nath Sharma (International Journal of Pharma and Bio Sciences, 2022)
Fluoride water problem is very common in all areas of world including India. The deleterious effects of fluoride on bones causes fluorosis. This problem arises mainly due to gradual lowering of ground water level, which is merely responsible for degrading water quality. The hand pumps of many areas are restricted for use due to excess fluoride in their water. In a country like India, it is very tough to provide pure drinking water to all. Hence this study is designed to study the effect of fluoride on biochemical parameters in albino rats, the mammalian model. The aim and objective of this study is to evaluate combination of two antioxidants viz. Tamarindus indica (rich source of vitamin C) and vitamin D against fluoride toxicity in mammals for which albino rat is used as model. Tamarindus have significant amount of antioxidants and vitamin D also have immunity and healing properties, hence this can be a reason behind their cumulative ameliorative effect against sodium fluoride intoxication. Further, the effect of fluoride can be minimized or ameliorated using some antioxidants and vitamins. For this purpose, the fluoride intoxicated rats were observed for possible amelioration by Tamarindus indica and vitamin D supplementation. The fluoride intoxication showed altered biochemical parameters like serum protein, SGOT, SGPT, ACP, ALP and LDH.